Correlation between international commodity prices and BDI index - Li, Jiayi (Nanyang Technological University, 2022)
The Baltic Dry Index (BDI), as a standard indicator reflecting the general performance of international dry bulk freight rates, has been highly referred to by the shipping and international trade communities. Therefore, an in-depth analysis of the variation pattern of the BDI index and its correlation with other economic variables is vital for shipping enterprises to make wise decisions in risk management and freight rate forecasting. The content consists of three aspects: Firstly, the factors influencing the variation of the Baltic Dry Index are explained in detail. Commodities including iron ore, thermal coal, soybean and crude oil are closely related to the international dry bulk shipping market and thus are the major research objects. The mechanism of the interaction between these four commodities and the BDI index is analyzed. Secondly, linear regression analysis is applied to investigate the relationship between the price of iron ore, thermal coal, soybean and crude oil and the BDI index. Thirdly, based on the study of the correlation between the four commodities and the BDI index, strategies are provided for shipping enterprises to forecast the trend of freight rate movement.